5(2x-3)-4(x-1)=

Simple and best practice solution for 5(2x-3)-4(x-1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(2x-3)-4(x-1)= equation:


Simplifying
5(2x + -3) + -4(x + -1) = 0

Reorder the terms:
5(-3 + 2x) + -4(x + -1) = 0
(-3 * 5 + 2x * 5) + -4(x + -1) = 0
(-15 + 10x) + -4(x + -1) = 0

Reorder the terms:
-15 + 10x + -4(-1 + x) = 0
-15 + 10x + (-1 * -4 + x * -4) = 0
-15 + 10x + (4 + -4x) = 0

Reorder the terms:
-15 + 4 + 10x + -4x = 0

Combine like terms: -15 + 4 = -11
-11 + 10x + -4x = 0

Combine like terms: 10x + -4x = 6x
-11 + 6x = 0

Solving
-11 + 6x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '11' to each side of the equation.
-11 + 11 + 6x = 0 + 11

Combine like terms: -11 + 11 = 0
0 + 6x = 0 + 11
6x = 0 + 11

Combine like terms: 0 + 11 = 11
6x = 11

Divide each side by '6'.
x = 1.833333333

Simplifying
x = 1.833333333

See similar equations:

| .64=(x-26.5) | | 7-3(a+4)=8+a | | .1=(x-26.5)/6.4 | | 7-3(a+4)=8+4 | | e^2x=11 | | 3y+14=7 | | x(y-1)dx+y(x+1)dy=0 | | 8-(x-14)= | | 2x/0=2 | | 4P-2=12+2P | | 4N-26=-50+7N | | A+(A-3)=(A-5)-(A+2) | | X+x-5=21 | | 0.0500=log(x) | | -100=11x^2+13x-28 | | 5.17p^2-7.47p=9 | | -0.008x^2-0.88x+5=0 | | 0.3x+0.4y=1.2 | | 6m^2=13m-28 | | -1(z+4)=2 | | A=6x+5 | | 7x^2-14x-58=-2 | | 8.75=n+5.61 | | 7.5p=20 | | 5a-3-8a-1+6a+4= | | 5(a+5)+6(6a+2)= | | 4x^2+41x+98=-2-3x | | 39=13w | | 2(5x-3)=4(2x-1) | | xy-y-x^2+1=4 | | xy-x-y-1=0 | | 2.4=m+9.7 |

Equations solver categories